2006
DOI: 10.1161/01.str.0000229900.88186.1a
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Level of Effort of the Plantar Flexors, Hip Flexors, and Extensors During Gait in Hemiparetic and Healthy Individuals

Abstract: Background and Purpose-Muscle weakness is recognized as a key factor in gait performance of poststroke individuals, but its impact on lower-limb muscular effort has been scarcely studied. The aims of this study were to compare the level of effort of the lower limbs of hemiparetic and able-bodied individuals and to assess the effect of side, cadence, and muscle group. Methods-Seventeen chronic hemiparetic participants (7 females and 10 males) with a mean age of 60.5Ϯ13.4 years were assessed when walking. They w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…Also, Simon and Ferris 21 demonstrated in hemiparetic subjects that, during an isometric force-matching task on a leg press machine, there was no significant difference between limbs when normalizing the forces produced by those obtained in bilateral maximum voluntary contractions. In addition, Milot et al 23 found that poststroke individuals during gait presented similar bilateral levels of effort estimated by a muscular utilization ratio, an index that expresses the relative involvement of a muscle in a functional task according to its maximal strength. These results suggest that the effort rather than the loading could be a dominant factor guiding muscle activation in hemiparetic individuals during functional tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Simon and Ferris 21 demonstrated in hemiparetic subjects that, during an isometric force-matching task on a leg press machine, there was no significant difference between limbs when normalizing the forces produced by those obtained in bilateral maximum voluntary contractions. In addition, Milot et al 23 found that poststroke individuals during gait presented similar bilateral levels of effort estimated by a muscular utilization ratio, an index that expresses the relative involvement of a muscle in a functional task according to its maximal strength. These results suggest that the effort rather than the loading could be a dominant factor guiding muscle activation in hemiparetic individuals during functional tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Although some authors have already reported neuromotor dysfunctions in the ipsilesional limbs when compared to healthy controls (Hall et al, 2011;Lamontagne et al, 2002;Lamontagne et al, 2000;Milot et al, 2006), they explained the dysfunction as a compensatory strategy rather than as a consequence of the lesion (Higginson et al, 2006;Lamontagne et al, 2002;Lamontagne et al, 2000).…”
Section: -Introductionmentioning
confidence: 96%
“…Although this line of reasoning is supported by neuroscientific knowledge, the research involving stroke subjects has given little attention to the comprehension of the behaviour of the ipsilesional side, usually referred to as the non-affected side (Hall et al, 2011;Lamontagne et al, 2002;Lamontagne et al, 2000;Milot et al, 2006;Peterson et al, 2010). Although some authors have already reported neuromotor dysfunctions in the ipsilesional limbs when compared to healthy controls (Hall et al, 2011;Lamontagne et al, 2002;Lamontagne et al, 2000;Milot et al, 2006), they explained the dysfunction as a compensatory strategy rather than as a consequence of the lesion (Higginson et al, 2006;Lamontagne et al, 2002;Lamontagne et al, 2000).…”
Section: -Introductionmentioning
confidence: 99%
“…In hemiparetic patients, this limitation is characterized by the equinovarus foot and inadequate muscular activation, leading to a compromise in support of the calcaneus in the initial support. This causes side support plant to increase and reduction in the boost phase, which leads to an abnormal pattern in the balance phase, characterized by the necessity for excessive hip flexion to keep the foot away from the floor (1,6,7) . The functional limitations developed by patients affected by upper and lower motor neuron injuries, directly interfere in their social and work life, thus reducing their abilities to perform them.…”
Section: Introductionmentioning
confidence: 99%